Кровососущие комары (Diptera, Culicidae) города Киева - Шеремет, В.П. (Вестник зоологии, 1978)
The fauna of blood-sucking mosquitoes is studied in Kiev. 27 species and subspecies belonging to 5 genera are found: Anopheles (2 species), Culiseta (2), Mansonia (1), Aedes (18), Culex (4). 18 of species are known as real or potential vectors of human disease agents.